2013
DOI: 10.1111/ane.12183
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric frontal lobe epilepsy: white matter abnormalities and cognitive impairment

Abstract: Children with FLE had white matter abnormalities mainly in posterior brain regions, not confined to the area of the seizure focus. Cognitively impaired children with FLE showed the most pronounced white matter abnormalities. These possibly reflect disturbed maturation and might be part of the etiology of the cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The mechanism behind the larger white matter volumes in children with FLE is unknown, but could include sprouting of white matter fibres in response to white matter damage or may reflect an accelerated myelination process. Using diffusion tensor imaging in this same patient cohort, we have also demonstrated increased myelination, thus preterm maturation, or an increase in axonal packing, in the children with FLE as compared to the controls .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The mechanism behind the larger white matter volumes in children with FLE is unknown, but could include sprouting of white matter fibres in response to white matter damage or may reflect an accelerated myelination process. Using diffusion tensor imaging in this same patient cohort, we have also demonstrated increased myelination, thus preterm maturation, or an increase in axonal packing, in the children with FLE as compared to the controls .…”
Section: Discussionmentioning
confidence: 57%
“…Another explanation for the larger cortex volumes might be that they result from disturbed maturation processes. In a diffusion tensor imaging study in the same patient cohort, we found that brain maturation in children with FLE, particularly the cognitively impaired patients, was disturbed . Both areas of increased myelination or increased axonal packing that could explain the larger cortex volumes, and areas of decreased myelination or decreased axonal packing that could explain the smaller cortex volumes, were seen throughout the whole brain.…”
Section: Discussionmentioning
confidence: 80%
“…Full text was screened in 71 cases and reference lists were inspected to detect additional studies not identified with the initial search. Forty-two studies met the inclusion criteria for the meta-analysis (Ahmadi et al, 2009, Andrade et al, 2014, Arfanakis et al, 2002, Braakman et al, 2014, Campos et al, 2015, Concha et al, 2005, Concha et al, 2007, Concha et al, 2009, Deppe et al, 2008, Diao et al, 2015, Diehl et al, 2008, Duning et al, 2010, Gao et al, 2012, Govindan et al, 2008, Gross et al, 2006, Holt et al, 2011, Hutchinson et al, 2010, Keller et al, 2011, Keller et al, 2012, Kemmotsu et al, 2011, Kemmotsu et al, 2014, Kim et al, 2011, Knake et al, 2009, Kori et al, 2013, Labate et al, 2015, Lee et al, 2013, Lee et al, 2014, Li et al, 2010, Liacu et al, 2012, Lin et al, 2008, Liu et al, 2011, Mao et al, 2011, McDonald et al, 2008, Meng et al, 2010a, Nilsson et al, 2008, Powell et al, 2007, Pustina et al, 2015, Rodrigo et al, 2007, Scanlon et al, 2013, Vulliemoz et al, 2011, Wang et al, 2010, Xiao et al, 2014). The total number of people with epilepsy and controls was 1027 and 1122, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Here the focus of interest has been the impact of epilepsy and its treatment on brain development and understanding the relationship of abnormalities in brain structure with commonly occurring cognitive, academic, and behavioral comorbidities (Besseling et al, 2014; Bonilha et al, 2014; Braakman et al, 2014, 2015; Ibrahim et al, 2014; Widjaja et al, 2014a; Widjaja et al, 2015; Widjaja et al, 2014b). …”
Section: Introductionmentioning
confidence: 99%